Perspective: lessons learned from the COVID-19 pandemic concerning the resilience of the population - Bruria Adini; Shaul Kimhi (BMC, 2023)
Abstract Background A vital stakeholder in the successful management of the COVID-19 pandemic is the public. The degree of involvement of the population in managing the pandemic, and the leadership perception of the public, had a direct impact on the resilience of the population and level of adherence to the issued protective measures. Main body Resilience refers to the ability to 'bounce back' or 'bounce forward' following adversity. Resilience facilitates community engagement which is a crucial component of combating the COVID-19 pandemic. The article highlights six insights recognized in studies conducted in Israel during and following the pandemic concerning the resilience of the country's population. (1) Contrary to varied adversities in which the community serves as an important support system to the individuals, this type of support was substantially impaired during the COVID-19 pandemic, due to the need to maintain isolation, social distancing, and lockdowns. (2) Policy-making during the pandemic should be based on evidence-based data, rather than on assumptions made by decision-makers. This gap led the authorities during the pandemic to adopt measures that were ineffective, such as risk communication based on 'scare tactics' concerning the virus, when the highest risk perceived by the public was political instability. (3) Societal resilience is associated with the public's behavior, such as with vaccine hesitancy and uptake. (4) Factors that affect the levels of resilience include, among others, self-efficacy (impacts individual resilience); social, institutional, and economic aspects as well as well-being (impact community resilience); and hope and trust in the leadership (impact societal resilience). (5) The public should be perceived as an asset in managing the pandemic, thus becoming a vital part of the 'solution'. This will lead to a better understanding of the needs and expectations of the population and an applicable 'tailoring' of the messages that address the public. (6) The gap between science and policymaking must be bridged, to achieve optimal management of the pandemic. Conclusions Improving preparedness for future pandemics should be based on a holistic view of all stakeholders, including the public as a valued partner, connectivity between policymakers and scientists, and strengthening the public's resilience, by enhancing trust in authorities.